2023
DOI: 10.3389/fgene.2022.1051762
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA and autophagy: Finding novel ways to improve the diagnostic management of bladder cancer

Abstract: Major fraction of the human genome is transcribed in to the RNA but is not translated in to any specific functional protein. These transcribed but not translated RNA molecules are called as non-coding RNA (ncRNA). There are thousands of different non-coding RNAs present inside the cells, each regulating different cellular pathway/pathways. Over the last few decades non-coding RNAs have been found to be involved in various diseases including cancer. Non-coding RNAs are reported to function both as tumor enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 166 publications
0
1
0
Order By: Relevance
“…A growing body of evidence indicates that long noncoding RNAs (lncRNAs) are expressed in most cancers with autophagy-modulating roles, impacting the survival of several cancers[ 12 , 13 ]. In their study[ 5 ], the authors found that hBD1-treated SW620 colon cancer cells exhibited upregulated expression of lncRNA TCONS_00014506.…”
Section: Modulation Of Autophagy By Long Noncoding Rnas In Sw620 Colo...mentioning
confidence: 99%
“…A growing body of evidence indicates that long noncoding RNAs (lncRNAs) are expressed in most cancers with autophagy-modulating roles, impacting the survival of several cancers[ 12 , 13 ]. In their study[ 5 ], the authors found that hBD1-treated SW620 colon cancer cells exhibited upregulated expression of lncRNA TCONS_00014506.…”
Section: Modulation Of Autophagy By Long Noncoding Rnas In Sw620 Colo...mentioning
confidence: 99%
“…The non-coding RNAs (ncRNAs) are less frequently expressed than the protein-coding genes, where their characteristic functional structures are well conserved across evolutionary timescales. It is well-established that ncRNAs function as both tumor enhancers and tumor suppressors in nearly all types of cancer ( Mattick and Makunin, 2006 ; Tantray et al, 2023 ). Despite these expression patterns, ncRNAs are precisely tuned to specific tissues or cancer types, regulating complex mechanisms ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%